Perbandingan Metode Rasional Dengan Kreatif Untuk Mendesain Alat Bantu Pasang Lampu - Rudy Firman Prakosa; Alva Edy Tontowi (Faculty of Engineering, Universitas Gadjah Mada, 2010)
Abstract This article discusses the result comparison of design process of lamp installation device using rational and creative methods and its usability analysis. The study was conducted through team recruitment, prototype development, prototype selection, and usability testing. The teams recruited involved creative team (K-team) consisting of experienced technical expert and non-exact students, and rational team (R-Team) consisting of exact students with knowledge in product design method. Result of prototype selection using weighted objectives method showedthat rational prototype produced higher total weight compared to that of creative prototype. Usability testing were also conducted in terms of rational and creative prototype methods. Usability testing involved learnability, error, efficiency of use, and satisfaction. Result of usability testing showed that rational prototype had higher efficiency of use, lower error, and higher satisfaction level. Therefore, rational method becomes better design process in lamp installation device. Keywords: product design, creative method, rational method, usability, device